Prophylactic effect of cefazolin on normal skin flora in patients harbored elective neurosurgery and surgery staffs - Homayoun Tabesh (Journal of Preventive Epidemiology, 2019)
Introduction: Surgical site infection (SSI) is one of the most important and dangerous complications of surgery. The normal skin flora is the most common source of the infection. Objectives: This study aimed to determine the prophylactic effect of cefazolin on normal skin flora in patients harbored elective neurosurgery and surgery staff. Patients and Methods: This analytical-descriptive study was carried on the samples taken from the hands of 100 personnel of operation room and the skin of incision site of 100 neurosurgical patients through swab and then cultured in blood agar and EMB (eosin methylene blue) medium. The effective antibiotic on dominant flora of skin was specified by antibiogram test. Results: Staphylococcus is consisted of 85.5% of strains grown in culture which included 80 cases methicillin resistance Staphylococcus epidermidis (MRSE) (40%), 11 cases Staphylococcus aureus (5.5%), 73 cases of S. epidermidis (36.5%), 7 cases Staphylococcus saprophyticus (3.5%) and 5 cases of methicillin resistance S. aureus (MRSA) (2.5%). The antibiotic resistance of the mentioned strains showed that 60% of MRSE strains, 100% of S. aureus strains and 67% of S. epidermidis strains were sensitive to cefazolin. Regarding ceftazidime, the sensitivity of gram-positive bacteria was 13% and 100% and 53.42% respectively. Conclusion: SSI is one of the main concerns of surgeons. Skin flora of patient or personnel’s hand are one of the main infectious sources, which are caused by Staphylococcus in 88% of cases because of not being full and sufficient sensitivity against cefazolin.